2016
DOI: 10.1016/j.celrep.2015.12.104
|View full text |Cite
|
Sign up to set email alerts
|

Tead and AP1 Coordinate Transcription and Motility

Abstract: SUMMARY The Tead family transcription factors are the major intracellular mediators of the Hippo-Yap pathway. Despite the importance of Hippo signaling in tumorigenesis, Tead-dependent downstream oncogenic programs and target genes in cancer cells remain poorly understood. Here we characterize Tead4-mediated transcriptional networks in a diverse range of cancer cells, including neuroblastoma, colorectal, lung, and endometrial carcinomas. By intersecting genome-wide chromatin occupancy analyses of Tead4, JunD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
203
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(220 citation statements)
references
References 49 publications
17
203
0
Order By: Relevance
“…In a mouse heart regeneration study, loss of salvador (sav) leads to transcriptional activation of several actin-related genes (Morikawa et al, 2015), suggesting that Yki may regulate actin regulators at the transcriptional level. Indeed, activation of migration-related genes by YAP/TEAD factors has also been observed in metastatic contexts (Liu et al, 2016). If this mechanism is conserved during larval WC, the specific Yki/Sd target genes that might be related to wound-induced migration have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mouse heart regeneration study, loss of salvador (sav) leads to transcriptional activation of several actin-related genes (Morikawa et al, 2015), suggesting that Yki may regulate actin regulators at the transcriptional level. Indeed, activation of migration-related genes by YAP/TEAD factors has also been observed in metastatic contexts (Liu et al, 2016). If this mechanism is conserved during larval WC, the specific Yki/Sd target genes that might be related to wound-induced migration have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the JNK downstream transcriptional factors, Activation Protein-1 family genes (AP-1), D-Jun and D-Fos, are required for larval WC (Lesch et al, 2010). Jun physically interacts with TEAD4 in colon cancer cells (Liu et al, 2016) and could potentially interact directly with Yki to regulate transcription as observed in cancer cells (Verfaillie et al, 2015; Zanconato et al, 2015). Some of the transcriptional targets that shared AP-1 and TEAD binding sites include actin regulators (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6D), and expression of E6 in NIKS did not increase the CTGF mRNA levels (data not shown), suggesting different requirements for coactivators between the two promoters. We speculate that YAP/TAZ are the limiting factors for TEAD-mediated CTGF transactivation, while coactivators other than YAP/TAZ, such as Vgll (35,36) and SRC3 (37,38), might be involved in A3B transactivation by TEAD. In support of this scenario, YAP and constitutively active YAP (5SA) only modestly activated the A3B promoter (Fig.…”
Section: Figmentioning
confidence: 99%
“…A genome-wide ChIP sequencing study revealed that TEAD4 binds to its own promoter and that YAP is required for TEAD4 expression (38), which suggests a positive-feedback mechanism for TEAD4 expression through TEAD4/YAP. In that study, TEAD4 binding to the TEAD1 promoter was also demonstrated (38), suggesting that TEAD1 expression can be upregulated by TEAD4/ YAP. In agreement with these findings, we found that overexpression of YAP was associated with increased TEAD1/4 levels in NIKS-E6 (Fig.…”
Section: Figmentioning
confidence: 99%